Determination of fluoride in spices using microwave induced oxygen combustion - Sucman, E., Veterinarni a Farmaceuticka Univ., Brno (Czech Republic). Ustav Biochemie, Chemie a Biofyziky; Bednar, J., Veterinarni a Farmaceuticka Univ., Brno (Czech Republic). Ustav Biochemie, Chemie a Biofyziky (Acta veterinaria Brno, 2012)
This work describes a method used to determine fluoride concentrations in various kinds of spices using microwave-supported sample preparation in high pressure oxygen atmosphere followed by potentiometry with a fluoride ion-selective electrode. Parameters of the microwave device for combustion procedure were checked and optimized in order to find settings ensuring complete sample combustion and/or absorption of the analyte in the absorption solution. For the ion-selective electrode measurement, the technique of standard straight line was chosen. Concentrations of fluorides in spices and spice blends under investigation ranged from 3.15 mg/kg to 26.08 mg/kg. In order to check the accuracy of the method Certified Reference Material Fluoride in Vegetation NIST 2695 was used and a good agreement between certified and found values was found. The precision expressed as the relative standard deviation ranged from 0.6% to 5.0%. The method is fast, accurate and reliable for this kind of analysis.